Hypogonadism and visceral obesity in men are full–fledged components of the metabolic syndrome - E. A. Troshina; Р. A. Terekhov (Ожирение и метаболизм, 2023)
Hypogonadism in men can cause the development of obesity, primarily abdominal, associated with high cardio-metabolic risks. Chronic obesity, in turn, almost inevitably leads to the manifestation of hypogonadism, which requires treatment and aggravates cardiovascular risks. Testosterone therapy, prescribed according to indications, has a significant positive effect not only on a man’s sexual function, but also on body weight, carbohydrate and lipid metabolism, bone metabolism and the emotional component of men’s health. The improvement of many metabolic parameters in men with verified hypogonadism occurs against the background of fairly long-term testosterone therapy. Hypogonadism and visceral obesity are now considered as components of the metabolic syndrome, mutually burden each other and require a comprehensive therapeutic approach.